AIRFLOW EVALUATION IN CLASSROOM DURING COVID-19 PANDEMIC (DIMENSI: Journal of Architecture and Built Environment, 2022)
The COVID-19 pandemic that hit Indonesia caused transition of the education process to online in 2020. The government seeks to improve the quality of student education in this pandemic era by preparing limited face-to-face learning. It is crucial to conduct a study on air because it is one of the mediums used to transfer viruses. This research took one sample of a classroom at SDN 27 North Pontianak. This research uses a Computational Fluid Dynamics simulation to display the air flow conditions of a room. The results showed that the fastest wind speed in the class ranged from 0.12 m/s to 0.44 m/s with green, yellow and red parameter color.  The slowest wind speed was 0.01 m/s to 0.12 m/s with blue and green parameter color. The parameter shows levels are within limits suggested by ASHRAE and the effect of the availability of smooth air circulation for the classroom and stable air change. They were limiting the virus ability to spread by improving airflow. Rapid air exchange in the classroom lowers the risk of infection for students and teaching staff.